A Navel Analysis of GNSS for Monitoring the Position of Trains - Yakaiah, P; Nishanth Rao, K; V.S. Prasad, S; Ramesh Reddy, G; Raveendranadh, B; Nagarjuna, T (International Journal of Engineering and Technology, 2018)
This Proposed paper using the technique of Navigation system that is Global navigation satellite system[1-2], which are usable to reach the trains in accurate time. The performance of these system is able analyze the based on reliability and maintainability. In this paper presented the operation of receiver navigation system, and also analyze the water levels on the railway track, and also identifying the accidents, and the information will be sent to respective registered mobiles.Â Â